Relative Kinetic Reactivities of Boronic Acids and Boronate Ions toward 1, 2‐Diols. Issue 14 (11th April 2014) - Okamoto, Takuya; Tanaka, Asumi; Watanabe, Eisuke; Miyazaki, Takehiro; Sugaya, Tomoaki; Iwatsuki, Satoshi; Inamo, Masahiko; Takagi, Hideo D.; Odani, Akira; Ishihara, Koji
Abstract: The following reaction systems, with and without proton ambiguity, were set up for direct measurements of the rate constants of borate and boronate ions: boric acid [B(OH)3 ] and 4, 5‐dihydroxy‐1, 3‐benzenedisulfonic acid disodium salt (Tiron); 3‐nitrophenylboronic acid [3‐NO2 PhB(OH)2 ] and Tiron; phenylboronic acid [PhB(OH)2 ] and 4‐nitrocatechol; boric acid and 4‐nitrocatechol. Each rate constant for boric or boronic acid is larger than that for the conjugate borate or boronate ion for the reaction systems without proton ambiguity. These results explicitly indicate that the widespread belief that the rate constants of boronate ions are several orders of magnitude larger than those of the conjugate boronic acids is erroneous. The relative kinetic reactivities of RB(OH)2 and RB(OH)3 – were investigated in relation to the linear free energy relationships between the rate constants and acidities of the boronic acids and diols. Abstract : Kinetic results clearly show that boronic acids are more reactive than their respective conjugate boronate ions. This corrects the erroneous conclusion that the boronate ion reacts faster than its conjugate boronic acid by at least several orders of magnitude. The relative kinetic reactivities of boric acid and boronate ions are discussed in terms of mechanistic differences.